Pengaruh Ukuran Perusahaan, Profitabilitas dan Auditor Switching Terhadap Audit Delay Pada Bursa Efek Indonesia - Annisa Annisa; Maizul Rahmizal (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The purpose of this study was to determine the effect of company size, profitability and auditor switching on audit delay in basic industrial and chemical soup manufacturing companies on the Indonesian Stock Exchange (BEI). The population is 31 manufacturing companies in the basic industrial sector and chemicals on the IDX. Using purposive sampling technique was applied to determine the sample. The sample in this study were the basic industrial and chemical soup manufacturing companies listed on the IDX and met the criteria. The number of samples used was 93 financial statements based on predetermined criteria. Data were collected using the documentation method measured by a ratio scale. The results showed that company size has a positive and significant effect on audit delay which is indicated by a significant value of 0.0462, profitability has a significant negative effect on audit delay with an alpha value of 0.0047, and auditor switching has no significant effect on audit delay. with negligent 0.5687